The Effect of the Implementation of Audit Tools and Linked Archives System (ATLAS), Independence, and Audit Fees on Audit Quality in Public Accounting Firms in Cirebon City - Syafiq, Achwan Muhammad; Indriyani, Rinni; Sari, Fitriya (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Audit quality is a crucial aspect in ensuring the credibility of financial statements, especially in the digital era where information technology plays an important role in supporting the audit process. One of the innovations used is the Audit Tools and Linked Archives System (ATLAS), which is designed to help auditors compile working papers efficiently and effectively. This study aims to analyze the effect of ATLAS implementation, auditor independence, and audit fees on audit quality at public accounting firms in Cirebon City. This study uses an explanatory quantitative approach with a Likert scale questionnaire as the instrument. The research population includes all auditors working at two active public accounting firms in Cirebon City, namely Indra Wiguna Marthanu, CPA and Kaslani, MM., CPA, so the census technique was used for sample selection. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression to test the simultaneous and partial effects of independent variables on audit quality. The results showed that the implementation of ATLAS and audit fees had a positive and significant effect on audit quality, while auditor independence did not show a significant partial effect. Simultaneously, the three independent variables had a significant effect on audit quality. These findings emphasize the importance of integrating the application of audit technology, adequate compensation, and auditor professionalism in improving audit quality. This study provides practical implications for KAP management in making decisions related to technology, audit fees, and auditor development to improve the credibility of financial reports.